The Vaccination Fear Scale (VFS-6): Adaptation, Cross-Cultural Validation, and Invariance among Genders and Six Different Cultures, Applying Classical Test Theory (CTT) and Item Response Theory (IRT) - Olga Malas; Nada Mallah Boustani; Mirko Duradoni; Dayo Omotoso; Asiye Şengül Avşar; Anastasiia Shyroka; Giulia Colombini; Angel Blanch (MDPI AG, 2024)
The coronavirus disease 2019 (COVID-19) pandemic had a meaningful impact on several areas of human activity. With respect to psychological assessment, the requirements to study the fear of vaccination as a means to diminish negative behaviour towards vaccination had been reported. This study aimed to evaluate the factorial invariance of the six-item Vaccination Fear Scale (VFS-6) across individuals and cultures. To achieve this goal, a sample of university students was recruited (n = 2535; mean age = 20.59, SD = 2.04; males: 26.75%, females: 73.25%) from Spain (n = 388; 15.3%), Italy (n = 376; 14.83%), Lebanon (n = 487; 19.21%), Nigeria (n = 561; 22.13%), Turkey (n = 410; 16.17%), and Ukraine (n = 313; 12.34%). The results showed that the most appropriate factorial structure, exhibiting excellent fit indices, was a model with two correlated factors (cognitive symptoms: items 1, 2, and 4; somatic symptoms: items 3, 5, and 6) for both the total sample and individual samples from each country and language (Spanish, Italian, Arabic, English, Turkish, and Ukrainian). Notably, the VFS-6 demonstrated configural, metric, scalar, and strict invariance across sex. Regarding countries and languages, configural invariance was observed between them. Also, metric invariance was observed between Spain, Italy, and Ukraine and between Lebanon, Nigeria, and Turkey, which indicates the presence of two well-differentiated groups of countries and the possibility of inferential analysis between them. Item Response Theory analysis suggested an appropriate level of discrimination and difficulty of the test. These significant findings lay the groundwork for future investigations into vaccination fear across diverse cultural backgrounds, providing valuable insights for addressing vaccination-related concerns worldwide.